Perspektif Masyarakat mengenai Trend Fashion di Era Zaman Modernisasi : Studi Kasus Organisasi Mahasiswa Desain Grafis Jakarta - Salman Alfarisi; Arief Ruslan (Lembaga Pengembangan Kinerja Dosen, 2026)
Modernization has changed how individuals present their identities, including through fashion. For Visual Communication Design (VCD) students, In addition to being a fundamental need, clothing is also a form of visual communication that reflects creativity, character, and social identity. This study explores how VCD students interpret fashion trends as expressions of self-identity in the modern era. Roland Barthes' semiotic analysis, which includes denotation, connotation, and myth, was used together with a descriptive qualitative method. Visual observation, in-depth interviews, and documentation were used to gather data. The subjects were VCD students from two Jakarta institutions. The analysis focused on visual fashion elements such as clothing type, color, pattern, and accessories as signs that construct social significance. The study's findings demonstrate that fashion among VCD students has a broader meaning beyond physical appearance. When it comes to denotation, fashion it’s represented using visual elements like clothing also accessories. At the connotative level, these elements create meanings such as casual, creative, expressive, and modern. Meanwhile, at the mythical level, fashion becomes a symbol of creative student identity, where appearance is used as a medium of nonverbal communication and self-expression. Fashion trends among VCD students are not only influenced by global trends and social media developments, but also by academic environments and visual culture on campus.